Infant weight gain and DXA-measured adolescent adiposity: data from the Japan Kids Body-composition Study - Yuki Fujita (Journal of Physiological Anthropology, 2021)
Abstract Background Rapid weight gain in early life is associated with adiposity later in life. However, there is limited information on the association between weight gain and body fat mass measured using precise methods. This study aimed to investigate whether weight gain is associated with body fat mass measured by dual-energy X-ray absorptiometry (DXA) in adolescents. Methods Participants of this retrospective cohort study were 423 adolescents born at full-term who were enrolled in the Japan Kids Body-composition Study. Anthropometric measurements related to pregnancy, delivery, and child health were obtained from the Japanese Maternal and Child Health Handbook. Fat mass in adolescents was measured with a DXA scanner. Weight gain was defined as the change in body weight from birth to age 1.5 years. Associations between birthweight and fat mass, and between weight gain and fat mass, were evaluated using multiple regression analysis. Results There was a significant positive association between weight gain from birth to age 1.5 years and fat mass in adolescents (boys: standardized regression coefficient (β) = 0.253, p < 0.01; girls: β = 0.246, p < 0.01), but not between birthweight standardized for gestational age and fat mass. Conclusion Children with a greater change in weight from birth to age 1.5 years tended to have increased fat mass in adolescence. Weight gain in early life has a greater impact on fat mass in adolescents than birthweight.